2016
DOI: 10.1016/j.ecresq.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Child-centered versus teacher-directed teaching practices: Associations with the development of academic skills in the first grade at school

Abstract: 2 Research Highlights How do child-centered versus teacher-directed practices promote academic skills development? Child-centered practices contribute positively to academic skills development at school.  The effect of child-centered practices on academic skills did not depend on the initial skill level  Teacher-directed practices are negatively associated with average and high reading skills. AbstractThis study examined the extent to which child-centered versus teacher-directed teaching practices predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 55 publications
4
64
0
2
Order By: Relevance
“…Meanwhile, Morrison and Connor (2002) found that children identified (at the start of Grade 1) as being at risk of developing RD had higher decoding skills after explicit teacher-managed instruction. Because the impact of instructional variables depends critically on children's existing level of ability (Lerkkanen et al, 2016;Morrison & Connor, 2002;Rutter & Maughan, 2002), it seems that those children most at risk would especially benefit from frequent literacy activities such as phonemic awareness and letter recognition in kindergarten (Hatcher et al, 1994). Consequently, the present study investigated the extent to which the frequency of such literacy activities in kindergarten corresponds to reading skills in Grade 1, and how a risk of RD may be a moderating variable in this correspondence.…”
Section: Kindergarten Literacy Activities and Reading Skillsmentioning
confidence: 95%
“…Meanwhile, Morrison and Connor (2002) found that children identified (at the start of Grade 1) as being at risk of developing RD had higher decoding skills after explicit teacher-managed instruction. Because the impact of instructional variables depends critically on children's existing level of ability (Lerkkanen et al, 2016;Morrison & Connor, 2002;Rutter & Maughan, 2002), it seems that those children most at risk would especially benefit from frequent literacy activities such as phonemic awareness and letter recognition in kindergarten (Hatcher et al, 1994). Consequently, the present study investigated the extent to which the frequency of such literacy activities in kindergarten corresponds to reading skills in Grade 1, and how a risk of RD may be a moderating variable in this correspondence.…”
Section: Kindergarten Literacy Activities and Reading Skillsmentioning
confidence: 95%
“…However, since word-level decoding reaches a high level of accuracy for most first grade students after only a few months of school (Lerkkanen et al 2004), students' commitment and motivation for reading to improve their fluency and comprehension is strongly supported already in first grade. Student gains and engagement in reading are encouraged, for example, through the availability of high-interest texts on multiple difficulty levels and by giving students the freedom to choose reading materials (Lerkkanen 2007;Lerkkanen et al 2016).…”
Section: Educational Systems and Reading Instruction In Estonia And Fmentioning
confidence: 99%
“…Hamre and Pianta 2010). Research has generally documented positive effects of childcentered (see a review by Cornelius-White 2007; Lerkkanen et al 2016) but also combined child-centered and teacher-directed Tang et al 2017) teaching practices on children's reading skills and motivation. However, using child-dominated teaching practices, characterized by giving too much freedom to children and too little guidance and support, tends to undermine children's reading and motivational development Tang et al 2017).…”
mentioning
confidence: 99%
“…Previous research has indicated that the development of reading skills is associated with a high level of child-centred teaching practices in the classroom (Lerkkanen, et al, 2016). Hence, teacher directed practices limited the opportunities for students to explore more than the low level cognitive strategies (such as memorising and translating to L1) in the classes that were observed.…”
Section: Transmission Teachingmentioning
confidence: 99%
“…Nur played the main role (Lerkkanen, et al, 2016). This type of teaching style is dominant in Brunei, which may be due to social-cultural expectations and roles.…”
Section: Transmission Teachingmentioning
confidence: 99%